Measuring Irish capital - Keeney, Mary J. (Economic & Social Studies, 2007)
Irish National Income and Expenditure Accounts do not contain information on capital stocks or capital services estimation. Estimates of the national capital stock and the depreciation of its fixed assets are basic macroeconomic aggregates and are integral components for many modelling exercises. This paper presents a detailed asset-level analysis of the stocks and depreciation of Irish fixed assets and the capital formation flows used to derive them. It applies an improved perpetual inventory methodology for calculating depreciation based on best practice employed for the US National Income and Product Accounts (NIPA). The paper shows how the three basic capital variables ? the net capital stock, consumption of fixed capital and capital services ? are linked through a standard equation for the value of an asset. The paper then presents estimates of the volume of capital services for the Irish economy as well as by asset type. The volume index of capital services (VICS) weights together the growth in the net stock of assets using shares that reflect the relative productivity of the different assets that make up the capital stock i.e. without controlling for the share of housing in the capital stock, total factor productivity will be overestimated for growth accounting purposes.
Paper presented at the 2oth Annual Conference of the Irish Economic Association, Bunclody, Co. Wexford, 2006
Keywords: Capital stock; Ireland; Econometrics; Capital services